Vocal fold leukoplakia recurrence risk model - Hanna Klimza; Joanna Jackowska; Wioletta Pietruszewska; Andrzej Porębski; Piotr Nogal; Agata Leduchowska; Małgorzata Wierzbicka (Scientific Reports, 2024)
Abstract The paper aims to define the variables that elevate the risk of VFL recurrence after adequate primary treatment, and to present the Recurrence Risk Model with practical conclusions to handle pVFL and rVFL. Out of 207 patients with primary vocal fold leukoplakia (pVFL), in 41 (19.8%) recurrent VFL (rVFL) was diagnosed. All patients were assessed by using a trans-nasal flexible video-endoscope using white light, and NBI. The primary measure of our study was to investigate whether morphological features of pVFL in WL, vascular pattern in NBI, and primary histological findings could predict VFL recurrence. To create a model of risk factors, two methods were used: logistic regression and a conditional inference decision tree. The study showed smoking was the factor that significantly and most strongly increased the likelihood of rVFL, as well as the older age groups have a greater odds of rVFL. Types IV, V and VI, according to Ni 2019 classification, were associated with a significantly higher risk of rVFL. The algorithm combining patients’ dependent variables and the combination of two classifications improves the predictive value of the presented VFL Recurrence Risk Model.